Neurojuridical Sciences from a neo-contemporary and futuristic perspective. - Ríos, Alfredo Adán (2021)
: This article is conducted according to a documentary theoretical investigation under a proposal that claims to have foundations of realistic orthodox scientific rigor because it is not a science fiction novel rather it is a realistic framework of what happens in the neo-contemporary progress to axioms Futurists that can be seen as retro-futuristic phenomena in terms of the applicability of the sciences of "complexity" as they call it today for the progress of neuro-legal sciences at an international and national level in any entity. This in order to see the scope before a critical point in the face of its infinitesimal axioms that collaborative fields of high scientific specialty can provide, of which are the experimental cognitive theoretical neurophysics in auxiliary support to the evolutionary and biophysically inspired computational cognitive neurosciences. Its primary scope is to recapitulate the greatest advances from a current perspective of the developments that the scientific community wants to achieve to support said theoretical application fields from which this documentary contribution can be based and a theoretical proposal of how these advances can reach their point evolution critic to his ultimate axiom of development. The relevant and important disciplines to be investigated are: Theoretical physics based on the neurophysics of human cognition. Computational cognitive neuroscience Cognitive sciences Neurolaw and applied science. The priority of this work is that the scientific community that works at professional levels in the field of neurojuridical sciences is open to new challenges such as application changes to this science of change and social order. Therefore, at the same time that science and technology evolve, as well as consciousness to the human mind, the changes undoubtedly exceed those of science fiction since it is a frame of reference of objective reality. Finally, there is the scientific task of only making an objective contribution to current events and probabilities that may arise over time in the field of neuro-legal science worldwide.